The effect of dual inflammation on the acute phase clinical outcomes of schizophrenia patients with comorbid COVID-19 - Jiahui Zhu; Jiamin Shao; Peng Wang; Yuan Liu; Gangming Cheng; Qi Zhou; Zhuoran Li; Jiayi Li; Mingqia Wang; Zhuokai Zhang; Xuan Dong; Chuan Shi (Brain, Behavior, & Immunity - Health)
Background and hypothesis: Inflammation plays a crucial role in pathological mechanisms in schizophrenia (SZ) and the coronavirus disease 2019 (COVID-19), but the impact of dual inflammation on SZs’ clinical outcomes is poorly understood. This study aimed to investigate whether dual inflammation impacts acute phase outcomes in patients with schizophrenia comorbid with COVID-19 (COVID-SZs). Study design: A total of 114 SZs and 49 COVID-SZs were recruited for this study. Plasma samples were collected and analyzed for levels of routine blood and inflammatory cytokines from all the participants. Then clinical symptoms, cognitive performance, and functional assessments were conducted at recruitment. One-way analysis of covariance examined the differences in inflammatory cytokines and correlation analyses examined the relationship between inflammatory cytokines and clinical outcomes. Study results: After controlling for age, gender, substance use status, and antipsychotic medications, levels of inflammatory cytokines increased in COVID-SZs groups compared to SZs groups. There were significantly higher total Positive and Negative Syndrome Scale (PANSS) scores and positive PANSS scores in COVID-SZs groups compared to SZs. As for cognitive performance, the COVID-SZs group had significantly worse performance in processing speed and attention than the SZs. The COVID-SZs group had significantly worse health status compared to the SZs. There were significantly different correlation patterns between the severity of psychiatric symptoms and inflammatory cytokines in COVID-SZs and SZs group. Conclusions: Findings indicate that dual inflammation exacerbates the acute phase clinical outcome of COVID-SZs. Suggesting a combined anti-inflammatory drug or the use of potentially anti-inflammatory antipsychotics in the acute phase of treatment to mitigate central nervous system damage. Regular monitoring of inflammatory marker levels can help reduce the risk of fluctuating psychiatric symptoms in patients with schizophrenia caused by inflammatory storms.